2010
DOI: 10.1016/j.hal.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial blooms and the occurrence of the neurotoxin, beta-N-methylamino-l-alanine (BMAA), in South Florida aquatic food webs

Abstract: Recent studies demonstrate that most cyanobacteria produce the neurotoxin beta-N-methylamino-Lalanine (BMAA) and that it can biomagnify in at least one terrestrial food chain. BMAA has been implicated as a significant environmental risk in the development of neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, and Amyotrophic Lateral Sclerosis (ALS). We examined several blooms of cyanobacteria in South Florida, and the BMAA content of resident animals, including species used as human fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
174
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(181 citation statements)
references
References 71 publications
6
174
1
Order By: Relevance
“…No large-scale monitoring in surface waters is conducted to determine the locations and extent of nutrient loading associated with predominantly non-saline domestic wastewater injected into aquifer zones of higher salinities because of the unsupported presumptions that aquifer-injected wastewater and other fluids don't discharge contaminants to surface waters, such as the near-shore coastal waters in southeast Florida, where coral reefs and federally threatened and endangered species once thrived. These HABs have been increasing in frequency and intensity in south Florida surface waters, with neurotoxins and expanses of benthic macroalgae becoming serious forms of HAB in south Florida (Barile, 2004;Brand & Compton, 2007;Brand, Pablo, Compton, Hammerschlag, & Mash, 2010;Lapointe & Barile, 2001). Benthic macroalgae are more difficult to detect and track from the surface than planktonic blooms, such as Florida's red-tide events.…”
Section: Background Of Aquifer Injection Wells and Submarine Groundwamentioning
confidence: 99%
“…No large-scale monitoring in surface waters is conducted to determine the locations and extent of nutrient loading associated with predominantly non-saline domestic wastewater injected into aquifer zones of higher salinities because of the unsupported presumptions that aquifer-injected wastewater and other fluids don't discharge contaminants to surface waters, such as the near-shore coastal waters in southeast Florida, where coral reefs and federally threatened and endangered species once thrived. These HABs have been increasing in frequency and intensity in south Florida surface waters, with neurotoxins and expanses of benthic macroalgae becoming serious forms of HAB in south Florida (Barile, 2004;Brand & Compton, 2007;Brand, Pablo, Compton, Hammerschlag, & Mash, 2010;Lapointe & Barile, 2001). Benthic macroalgae are more difficult to detect and track from the surface than planktonic blooms, such as Florida's red-tide events.…”
Section: Background Of Aquifer Injection Wells and Submarine Groundwamentioning
confidence: 99%
“…As an example, BMAA concentrations reported for food webs in South Florida (high µg/g up to mg/g dry weight levels [82]) were orders of magnitude higher than those reported for the Baltic Sea (mostly ng/g dry weight [83]). The cause of these conflicting results was attributed to the different analytical methods used, although there was initially little consensus on what would be the most suitable method for BMAA analysis (e.g.…”
Section: General Introductionmentioning
confidence: 75%
“…concentrations in the two food web studies performed so far differ greatly: those reported for the Baltic sea (mostly ng/g dry weight (DW), [83]) were a few orders of magnitude lower than those for Florida (high µg/g up to mg/g DW [82]). (Table 5.1) could be that BMAA is produced in detectable amounts in some cyanobacteria and not in others.…”
mentioning
confidence: 84%
See 2 more Smart Citations